Vehicle-pedestrian Instance Segmentation Algorithm Based on Improved YOLOv8n-seg - Fang, Siwen; Zhang, Xinhe; Su, Bochao; Zhu, Wenxuan (Engineering letters, 2025)
In the field of autonomous driving, the rapid and precise perception of the environment, along with effective segmentation of vehicles and pedestrians, is a critical area of research. The complexity of real-world scenes, often characterized by occlusions, can lead to suboptimal segmentation results. Moreover, the computational demands of existing models require substantial resources and time for processing image data. In autonomous driving systems, timely perception and decision-making are essential; computational delays can hinder vehicle responsiveness and increase the risk of driving errors. To enhance the performance of vehicle-pedestrian segmentation, this paper proposes a novel single-stage instance segmentation approach based on an improved YOLOv8n-seg model. This improvement involves redesigning the bottleneck module in the core C2f module of YOLOv8n-seg and replacing the feature fusion layer with a Bidirectional Feature Pyramid Network (BiFPN) structure. Evaluations conducted on the Cityscapes dataset demonstrate that our method achieves a 3.1% increase in the mAP50-95mask value and a 1% reduction in FLOPs compared to the original YOLOv8n-seg. Furthermore, experiments on the COCO subset show that our approach achieves a mAP50mask of 55.6%, mAP50-95mask of 34.2%, and significantly improves segmentation performance under various real-world conditions. Consequently, our approach not only enhances segmentation accuracy but also reduces computational complexity, effectively meeting the real-time requirements for vehicle segmentation in autonomous driving applications.